Pengaruh Implementasi Program Kampus Mengajar Angkatan 6 Terhadap Kompetensi Pedagogik Mahasiswa FKIP Universitas Flores - Karmelia Bof (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2024)
This study aims to find out: (1) the implementation of the Teaching Campus Program Batch 6, (2) the pedagogic competence of the Teaching Campus students of Batch 6 FKIP University of Flores, and (3) the influence of the implementation of the Teaching Campus Program on the pedagogic competence of FKIP students of the University of Flores. The type of research is quantitative research with data collection techniques using questionnaires and documentation studies. The subject of the study is a student of the Teaching Campus Batch 6 FKIP University of Flores.The results of the study showed that the implementation of the teaching campus program was in the good category overall, with an average score of 59.90, of which 63% (19 respondents) were in the good category and 37% (11 respondents) were in the very good category. Furthermore, the pedagogic competence of the 6th batch of FKIP FKIP University of Flores consisted of 50% (15 respondents) with the good category and 50% (15 respondents) with the very good category. Based on the results of the analysis, the average value of pedagogic competence is 60.03, which means that overall, students have good pedagogic competence . In addition, it is proven that the implementation of the Teaching Campus Program has a significant influence on the pedagogic competence of FKIP students at the University of Flores. This is in accordance with the results of the t-test with a t-count value of 2.149 (greater than the ttable 2.048) and a significance value of 0.040 < 0.05. The variable of the Teaching Campus Program explains that around 14.2% of its influence on students' pedagogic competence, while the remaining 85.8% is influenced by other factors outside the research.